2020
DOI: 10.34172/ps.2019.61
|View full text |Cite
|
Sign up to set email alerts
|

Virgin Coconut Oil Ameliorates Colchicine Induced Cognitive Dysfunction- A Preclinical Study

Abstract: Background : Virgin coconut oil (VCO) has been identified as a potential cognitive strengthener associated with Alzheimer’s disease (AD). It contains medium chain fatty acids (MCFA) which are absorbed and easily metabolized by the liver to form ketone bodies. Ketone bodies are converted to acetyl Co-A in the brain which then enters the citric acid cycle to provide ATP and also serves as precursors of acetylcholine in neurons. Sunflower oil (SO) contains poly unsaturated fatty acids which has both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“… 34 Moreover, the neuroprotective antioxidant activities of coconut oil have been attributed to its polyphenolic content, which is present in higher concentrations in virgin oils (such as caffeic acid, gallic acid, quercetin, myricetin glycoside catechin, methyl catechin, dihydrokaempferol, ferulic acids, and p-coumaric acid). 35 …”
Section: Neurological Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 Moreover, the neuroprotective antioxidant activities of coconut oil have been attributed to its polyphenolic content, which is present in higher concentrations in virgin oils (such as caffeic acid, gallic acid, quercetin, myricetin glycoside catechin, methyl catechin, dihydrokaempferol, ferulic acids, and p-coumaric acid). 35 …”
Section: Neurological Disordersmentioning
confidence: 99%
“…34 Moreover, the neuroprotective antioxidant activities of coconut oil have been attributed to its polyphenolic content, which is present in higher concentrations in virgin oils (such as caffeic acid, gallic acid, quercetin, myricetin glycoside catechin, methyl catechin, dihydrokaempferol, ferulic acids, and p-coumaric acid). 35 Based on the literature, there is enough evidence on the link between the Mediterranean diet of which EVOO is the main constituent, and lower risk of AD. Studies have shown that adding EVOO addition to the AD model mice diet before the onset of pathology resulted in the restoration of blood−brain barrier function, reduction of the levels of total brain tau, and amyloid-β; it also improved the cognitive behavior in the mice.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…Consumption of medium-chain fatty acid (MCFA) such as VCO reduces the risk factor of cardiovascular diseases (Oh K et al, 2005), lowers the blood pressure (Nurul-Iman et al, 2013) and blood sugar (Babayan, 1987). The MCFA presents in the VCO can be acted as an energy source for the brain through metabolizing it into the ketone bodies which are converted to acetyl Co-A to produce ATP and it acts as precursors for acetylcholine in neurons (John et al, 2020). Moreover, pure coconut scent is preserved in VCO with a high level of antioxidants and vitamins to improve the anti-carcinogenic activity of the human body (Nevin and Rajamohan, 2004).…”
Section: Introductionmentioning
confidence: 99%